2011
DOI: 10.1002/jts.20622
|View full text |Cite
|
Sign up to set email alerts
|

School‐based intervention programs for PTSD symptoms: A review and meta‐analysis

Abstract: This is a review and meta-analysis of school-based intervention programs targeted at reducing symptoms of posttraumatic stress disorder (PTSD). Nineteen studies conducted in 9 different countries satisfied the inclusionary criteria. The studies dealt with various kinds of type I and type II trauma exposure. Sixteen studies used cognitive-behavioral therapy methods; the others used play/art, eye movement desensitization and reprocessing, and mind-body techniques. The overall effect size for the 19 studies was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
104
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 40 publications
(21 reference statements)
4
104
0
3
Order By: Relevance
“…Furthermore, teachers may serve as a linking pin between families and clinical services as schools are children's most important entry point to mental health care (Farmer, Burns, Phillips, Angold, & Costello, 2003). One particular area in which teachers can be instrumental is in monitoring and supporting children's recovery from traumatic events (Rolfsnes & Idsoe, 2011). The large number of hours that teachers spend with children each week enables them to identify posttraumatic behavior change.…”
mentioning
confidence: 99%
“…Furthermore, teachers may serve as a linking pin between families and clinical services as schools are children's most important entry point to mental health care (Farmer, Burns, Phillips, Angold, & Costello, 2003). One particular area in which teachers can be instrumental is in monitoring and supporting children's recovery from traumatic events (Rolfsnes & Idsoe, 2011). The large number of hours that teachers spend with children each week enables them to identify posttraumatic behavior change.…”
mentioning
confidence: 99%
“…The movement has also been fueled by demonstrations of the effectiveness of school-based trauma-specific treatments in ameliorating traumatic stress reactions in youth (Rolfsnes & Idsoe, 2011). These drivers of the movement are reflective of SAMHSA's (2014) four key assumptions underlying trauma-informed approaches: (a) a realization of the widespread prevalence and impact of trauma, (b) a recognition of the signs of traumatic exposure and (c) a response grounded in evidence-based practices that (d) resists re-traumatization of individuals.…”
mentioning
confidence: 99%
“…Some treatments were effectively administered in group settings (Betancourt et al, 2012a; Pfeiffer & Goldbeck, 2017) or at school (Gupta & Zimmer, 2008; Ooi et al, 2016; Schauer, 2008; Tol et al, 2012). Other reviews (Newman et al, 2014; Rolfsnes & Idsoe, 2011) have reported moderate (Rolfsnes & Idsoe, 2011) to large (Newman et al, 2014) effect sizes for trauma-related psychotherapies in the group/school setting, even if they were provided by trained lay persons like teachers or social workers. A substantial number of affected school-aged refugee children could be reached this way, if effective interventions were available.…”
Section: Discussionmentioning
confidence: 98%